Leadership Development in Women STEM Students: The Interplay of Task Behaviors, Self-Efficacy, and University Training - Giuliani Coluccio; Sebastián Muñoz-Herrera; Elisa Adriasola; Elizabeth Escobar (Behavioral Sciences)
This study explores the relationship between task-oriented behaviors, self-efficacy, and leadership emergence in women STEM students, grounded in the context of prototypical leadership theory and self-efficacy theory. Prototypical leadership theory emphasizes the alignment of leadership behaviors with group expectations, which, in STEM fields, are often task-oriented. The research examines how task-oriented behaviors, such as planning, decision-making, and supervision, influence women’s self-perception of leadership ability and their subsequent emergence as leaders. Our results show a positive relationship between task-oriented behaviors and self-efficacy and a positive relationship between self-efficacy with leader emergence, with academic experience further ngthening this link. As students’ progress through their programs, engaging in more teamwork and leadership tasks, their self-efficacy enhances, leading to stronger leadership emergence. Also, we found an indirect effect from task-oriented behavior to leader emergence via self-efficacy. These findings have significant implications for fostering leadership in women, particularly in STEM. The study calls for educational programs to enhance opportunities for women to develop these behaviors early on, ensuring their growth into leadership roles in STEM fields.